Evolved Gas Analysis‐Mass Spectrometry to Identify the Earliest Organic Binder in Aegean Style Wall Paintings. (3rd September 2018) - Linn, Ravit; Bonaduce, Ilaria; Ntasi, Georgia; Birolo, Leila; Yasur‐Landau, Assaf; Cline, Eric H.; Nevin, Austin; Lluveras‐Tenorio, Anna
Abstract: An organic binder was identified in the painted fragments from the Canaanite palace of Tel Kabri, Israel. Recently dated to the late 18th century B.C.E. by 14 C, Tel Kabri is the most ancient of the Eastern Mediterranean sites in which Aegean style paintings have been found. The application of pigments was suspected to be using an organic binding medium, particularly for the Egyptian Blue pigment. Samples of blue paint were examined using evolved gas analysis‐mass spectrometry (EGA‐MS) in order to overcome the analytical challenges imposed by highly degraded aged proteinaceous materials. Egg was identified as the binder based on the presence of hexadecanonitrile and octadecanonitrile, confirming the use of a secco painting technique. Lysozyme C from Gallus gallus was detected by proteomics analysis, confirming the presence of egg. To our knowledge, this is the earliest use of egg as a binder in Aegean style wall paintings. Abstract : Analytische Pyrolyse (EGA‐MS) wurde erstmals zur Identifizierung des organischen Bindemittels in den ältesten Ägäischen Malereien aus der Bronzezeit (spätes 18. Jh. v. Chr.) aus dem Palast von Tel Kabri verwendet. MS‐basierte Proteomik bestätigte die Verwendung von Ei als Bindemittel der blauen Farbe, was die Vermutung stützt, dass eine Secco‐Maltechnik weitaus früher zum Einsatz kam als bisher angenommen.